EGGS PRODUCTION OF GROUPER HYBRID FOR SUPPORTING HATCHERY BUSINESS - Suko Ismi (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2017)
The grouper hatchery now has been widely developed, usually purchased eggs from the business that produces hybrid grouper eggs in accordance with the amount as needed. Eggs grouper that is currently in demand are eggs grouper cantang that is a cross-breed between female tiger grouper (Epinephelus fuscoguttatus) and male giant grouper (Epinephelus lanceolatus) and cantik that is a cross-breed between female tiger grouper and male grouper batik (Epinephelus Microdon). The purpose of this research is to get information about hybrid egg production activities, marketing and economics. The study was conducted in Buleleng regency in January-December 2015, data was taken from five hatchery or business that produces only hybrid grouper egg that is one business (A) in the village of Banyuasri, Buleleng district; Three businesses (B); (C) and (D) in the village of Penyabangan, Gerokgak district and the effort (E) in the village of Banyupoh, Gerokgak district, the data were analyzed descriptively. The results of the five businesses may produce as many eggs as five to eight times a year by the amount that can be marketed 24,200,000 - 44,500,000 eggs. The result of business analysis R / C ratio > 1 which means the business is profitable. Keyword: eggs, hatchery, hybrid, production, support